a)x supra 2√5=√15 supra 10
b)√6 supra x=√2 supra √6
c)x supra √2 - 3 supra √6=√2 supra √3
d)x supra √30 - √27 supra √10=2√30 supra 10
e)x(√5-√3)=5 supra √5 - 3+√3 supra √3 + 1
Astea 5 vrei.
[tex]\frac{x}{2\sqrt{5}}=\frac{\sqrt{15}}{10}[/tex]
[tex]10x=10\sqrt{3}\Rightarrow x=\sqrt{3}[/tex]
b)[tex]\frac{\sqrt{6}}{x}=\frac{\sqrt{2}}{\sqrt{6}}[/tex]
[tex]\sqrt{2}x=6 \Rightarrow x=\frac{6\sqrt{2}}{2}[/tex]
c)[tex]\frac{x}{\sqrt{2}}-\frac{\sqrt{3}}{\sqrt{2}}=\frac{\sqrt{2}}{\sqrt{3}}[/tex]
[tex]\sqrt{3}(x-\sqrt{3})=2\Leftrightarrow x\sqrt{3}-3=2 \Leftrightarrow x=\frac{5}{\sqrt{3}}[/tex]
d)[tex]\frac{x}{\sqrt{30}}-\frac{\sqrt{27}}{\sqrt{10}}=\frac{2\sqrt{30}}{10}[/tex]
[tex]\frac{x\sqrt{10}-9\sqrt{10}}{10\sqrt{3}}=\frac{6\sqrt{10}}{10\sqrt{3}}[/tex]
De unde x=15
e)[tex]x(\sqrt{5}-\sqrt{3})=\sqrt{5}-\frac{\sqrt{3}(\sqrt{3}+1)}{\sqrt{3}+1}[/tex]
[tex]x(\sqrt{5}-\sqrt{3})=\sqrt{3}-\sqrt{3}[/tex]
De unde x=1